Towards Conceptual Modelling Interoperability in a Web Tool for Ontology Engineering - Braun, Germán (2017)
The definition of suitable visual paradigms for ontology modelling is still an open issue. Despite obvious differences between the expressiveness of conceptual modelling (CM) languages and ontologies, many proposed tools have been based on UML, EER and ORM. Additionally, all of these tools support only one CM as visual language, reducing even more their modelling capabilities. In previous works, we have presented crowd as a Web architecture for graphical ontology designing in UML and logical reasoning to verify the relevant properties of these models. The aim of this tool is to extend the reasoning capabilities on top of visual representations as much as possible. In this paper, we present an extended crowd architecture and a new prototype focusing on an ontology-driven metamodel to enable different CMs visual languages for ontology modelling. Thus facilitating inter-model assertions across models represented in different languages, converting between modelling languages and reasoning on them. Finally, we detail the new architecture and demonstrate the usage of the prototype with simple examples.